Fabrication of Si3N4 ceramics by post-reaction sintering using Si–Y2O3–Al2O3 nanocomposite particles prepared by mechanical treatment. Issue 10 (1st August 2016) - Jeong, Kwangjin; Tatami, Junichi; Iijima, Motoyuki; Takahashi, Takuma
Abstract: Post-reaction sintering of a powder compact of Si and sintering aids is a useful technique for fabricating silicon nitride (Si3 N4 ) ceramics at low costs. In order to inhibit the inhomogeneous and uncontrollable exothermic nitridation of Si in the powder compact, Si–Y2 O3 –Al2 O3 nanocomposite particles are designed as an aid for post-reaction sintering. These Si–Y2 O3 –Al2 O3 nanocomposite particles are prepared via mechanical treatment applying high shear stress. Scanning electron microscopy (SEM) observations show that Y2 O3 and Al2 O3 particles are homogenously dispersed, and fixed to the Si particles. A green compact prepared using the Si–Y2 O3 –Al2 O3 nanocomposite particles results in lower electrical resistivity than that prepared using a powder mixed by wet ball-milling, which suggests that Si particles in the green compact prepared using the nanocomposite particles are isolated by Y2 O3 and Al2 O3 particles. The isolation of Si particles by the sintering aids successfully prevents the Si particles from melting and agglomerating during the nitridation process, resulting in a higher nitridation ratio and higher α-Si3 N4 phase content due to the inhibition of rapid heat transfer caused by the exothermic reaction. The nitridation ratio also increases with the applied power during mechanical treatment. As a result of firing the homogeneously nitrided powder compacts at high temperatures, Si3 N4 ceramics with homogeneous microstructure and improved density are successfully fabricated in this manner.